Leaders' personalities and the outcomes of democratic elections - King, Anthony, 1934-2017 (Oxford University Press, 2002)
Examining the importance, or non-importance, of the personalities of political leaders in determining the outcomes of democratic elections, this book argues that relatively few voters are swayed by candidates' personal characteristics.